2007
DOI: 10.1002/uog.5159
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal progesterone is associated with a decrease in risk for early preterm birth and improved neonatal outcome in women with a short cervix: a secondary analysis from a randomized, double‐blind, placebo‐controlled trial

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
150
2
5

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(165 citation statements)
references
References 31 publications
8
150
2
5
Order By: Relevance
“…(48) In 71 singleton gestations with prior PTB, vaginal progesterone 100mg suppositories daily between 24-34weeks was associated with significant reduction in incidences of PTB < 37 weeks (24% vs 50%; OR 3.11, 95% CI 1.13-8.53) and <34 weeks (5.4% vs 26.5%; OR 6.30, 95% CI 1.25-31.70), compared to placebo (49) In a meta-analysis, including 169 singleton gestations with prior PTB and TVU CL ≤ (8). Therefore screening women with singleton gestations with prior spontaneous PTB with TVU CL starting usually at 16 weeks and every 2 weeks until 23 weeks is suggested, so that cerclage can be offered for those who develop a TVU CL < 25mm.…”
Section: Vaginal Progesteronementioning
confidence: 99%
“…(48) In 71 singleton gestations with prior PTB, vaginal progesterone 100mg suppositories daily between 24-34weeks was associated with significant reduction in incidences of PTB < 37 weeks (24% vs 50%; OR 3.11, 95% CI 1.13-8.53) and <34 weeks (5.4% vs 26.5%; OR 6.30, 95% CI 1.25-31.70), compared to placebo (49) In a meta-analysis, including 169 singleton gestations with prior PTB and TVU CL ≤ (8). Therefore screening women with singleton gestations with prior spontaneous PTB with TVU CL starting usually at 16 weeks and every 2 weeks until 23 weeks is suggested, so that cerclage can be offered for those who develop a TVU CL < 25mm.…”
Section: Vaginal Progesteronementioning
confidence: 99%
“…41,42 Studies have suggested possible benefit with progesterone use in women with a history of preterm birth. 43 Two studies of women with a short cervical length have suggested the use of progesterone may reduce the risk of preterm birth, 44,45 however, further research is needed in this area. There is no evidence of benefit for this therapy in other high-risk asymptomatic groups, such as those with a uterine anomaly or excisional cervical treatment for dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, treatment of patients carrying a singleton gestation found to have cervical length <15mm at 20-25 weeks with micronized vaginal progesterone 200mg qhs resulted in a 44% decrease in preterm birth prior to 34 weeks [12]. The use of vaginal progesterone of different formulations to include 90mg gel [13], 200mg pessary [14] and 100mg suppository [15] to reduce the risk of preterm birth in twin gestations has been evaluated without success.…”
Section: Author Preterm Birth Risk Factor Gestational Age At Treatmenmentioning
confidence: 99%
“…Cerclage has been shown to reduce the incidence of recurrent preterm birth in women with a current singleton gestation and history of preterm birth when the cervix was found to be <15-25mm prior to 23-24 weeks [16][17]. Consequently, most experts use cervical length of 15-25mm as their threshold for cerclage placement in a patient with a prior spontaneous preterm birth [15,18]. Cerclage placement in women without a history of prior spontaneous preterm birth and short cervix has not been associated with a reduction in preterm birth [18] and use of cerclage in twin gestation with cervical length <25mm has been associated with a twofold increase in preterm birth [19].…”
Section: Cerclagementioning
confidence: 99%